Enhancing environmental decontamination and sustainable production through synergistic and complementary interactions of actinobacteria and fungi - Sáez, Juliana María (2025)
Actinobacteria and fungi are renowned for their metabolic diversity and adaptability to various environments, thus exhibiting significant potential for environmental decontamination and sustainable production. Both actinobacteria and fungi excel in producing diverse secondary metabolites and enzymes, offering valuable tools for industrial and environmental applications. Their ability to detoxify metals and degrade a wide range of organic pollutants, such as pesticides, hydrocarbons, and dyes, positions them as promising candidates for bioremediation. Recent shifts in microbiological sciences emphasize research on mixed microbial populations. Microbial interactions in mixed communities emulate natural processes and yield emergent properties such as stability, robustness, and enhanced metabolism. Co-cultures of actinobacteria and fungi harness a broader range of genes and metabolic capabilities through their distinctive interactions, opening new avenues for developing novel products and/or technologies. This review provides a critical analysis of the present status of knowledge regarding the potential of actinobacteria-fungi co-cultures with a particular focus on novel functionalities and heightened production efficiency. These consortia are promising in several fields, from environmental applications to the biosynthesis of industrially relevant metabolites and enzymes, and enhancements in agricultural production. Although challenges still exist, their potential to address complex problems has been demonstrated and deserves further investigation.